Analisis Kinerja Tenaga Pendidik dan Kependidikan (Dosen dan Karyawan) Pada STIMI Banjarmasin) - Anwar, Mahfuzil (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
This study aims to obtain empirical evidence on the performance of educators (lecturers), especially on the main task of implementing education and learning. In addition to educators of this research will also analyze the performance of education personnel (employees) in performing the task of serving students at STIMI Banjarmasin The hypothesis is Hypotesis I, The performance of educators (lecturers) is good, and Hypothesis II, the performance of educational staff (employees) on STIMI Banjarmasin is good. Through questionnaires submitted to respondents with indicators of learning with 5 items of questions, skills with 4 items of questions, assessment and workload with 2 items of questions, guidance and counseling with 2 items of questions, and learning resources with 2 items of questions, for educators (lecturers ) As many as 23 people. As for the education personnel (employees) as many as 8 people, with the indicator of responsibility with 3 items of questions, quality with 3 items of questions, quantity with 2 items of questions, and discipline with 2 question items. The results showed that for the performance of educators (lecturers) showed good results, while the performance of educational personnel (employees) showed good results.Keyword : lecturer performance, employees performance